Direction of Flap Rotation in Propeller Flaps: Does It Really Matter? - Song, Sinyoung; Jeong, Hyung Hwa; Lee, Yeonhun; Powers, Hollie; Suh, Young Chul; Christoffi, Phaedon; Suh, Hyunsuk Peter; Hong, Joon Pio Jp (Journal of Reconstructive Microsurgery, 2019)
Background This article investigates the effect of 180° rotating propeller flaps and evaluates whether each flap has a “preferable” rotating direction.Methods Part 1 evaluates the flap pedicle velocity and flow volume in neutral, 180°counterclockwise, and clockwise rotated position for 29 consecutive flaps. The data (velocity and volume) were divided into three groups: neutral, high value, and low value group then evaluated. Part 2 compares the outcome from the prospective study where a preferable rotation with high value was selected against 29 patients from 2012 to 2016 who had the same operation without selecting a preferable rotation direction.Results In part 1, the three groups (neutral, high value, and low value groups) showed mean velocity of 28.06 ± 7.94, 31.92 ± 10.22, 24.41 ± 8.12 cm/s, respectively, and mean volume of 6.11 ± 4.95, 6.83 ± 6.69, 4.62 ± 3.55 mL/min, respectively. The mean velocity and volume of the perforator in the high value group were significantly higher than that in the low value group (p = 0.0001). In part 2, although no statistical significance in the outcome was observed, there were two cases of total, two cases of partial flap loss, and three cases of wound dehiscence in the patients where preferable rotations was not selected compared with only two wound dehiscence for flaps with preferable rotation.Conclusion The velocity and flow of the flap are significantly different based on the rotation direction of the flap. Using the preferred rotation direction with statistically higher value of velocity and flow may increase the overall outcome of the propeller flap, especially where larger flaps are used.
Keywords: propeller flaps; rotation of flaps; perfusion of flaps